F8 intron 22 inversions and SNP rs73563631 in unrelated families with severe haemophilia A: clinical features and gene testing implications - Abelleyro, Miguel Martín; Rossetti, Liliana Carmen; Curto, María de los Ángeles; Radic, Claudia Pamela; Marchione, Vanina Daniela; Brasi, Carlos Daniel De (Thrombosis and Haemostasis, 2016)
Supplementary Material to this article is available online at www.thrombosis-online.com.